Continued Emissions of the Ozone‐Depleting Substance Carbon Tetrachloride From Eastern Asia. Issue 20 (18th October 2018) - Lunt, M. F.; Park, S.; Li, S.; Henne, S.; Manning, A. J.; Ganesan, A. L.; Simpson, I. J.; Blake, D. R.; Liang, Q.; O'Doherty, S.; Harth, C. M.; Mühle, J.; et al.
Abstract: Carbon tetrachloride (CCl4 ) is an ozone‐depleting substance, accounting for about 10% of the chlorine in the troposphere. Under the terms of the Montreal Protocol, its production for dispersive uses was banned from 2010. In this work we show that, despite the controls on production being introduced, CCl4 emissions from the eastern part of China did not decline between 2009 and 2016. This finding is in contrast to a recent bottom‐up estimate, which predicted a significant decrease in emissions after the introduction of production controls. We find eastern Asian emissions of CCl4 to be 16 (9–24) Gg/year on average between 2009 and 2016, with the primary source regions being in eastern China. The spatial distribution of emissions that we derive suggests that the source distribution of CCl4 in China changed during the 8‐year study period, indicating a new source or sources of emissions from China's Shandong province after 2012. Plain Language Summary: Carbon tetrachloride is one of several man‐made gases that contribute to the depletion of the ozone layer high in the atmosphere. Because of this, restrictions were introduced on the use of this ozone‐depleting substance, with the expectation that production should by now be close to 0. However, the slower than expected rate of decline of carbon tetrachloride in the atmosphere shows this is not the case, and a large portion of global emissions are unaccounted for. In this study we use atmospheric measurements of carbon tetrachloride from a site in East Asia to identify the magnitude and location of emissions from this region between 2009 and 2016. We find that there are significant ongoing emissions from eastern China and that these account for a large part of the missing emissions from global estimates. The presence of continued sources of this important ozone‐depleting substance indicates that more could be done to speed up the recovery of the ozone layer. Key Points: Emissions from eastern Asia region account for around 40% of global CCl4 emissions There has been no sustained decrease in emissions from the region since the introduction of production controls in 2010 Main source regions are in Jiangsu and Shandong provinces of China